The effect of reactor temperature and hydrogen flow rate on carbon nanofibers (CNFs) characterizations and their adsorption capacity - Abdul Halif, Norzilah; Ahmadun, Fakhru'l-Razi; Choong, Thomas Shean Yaw; Abdullah, Luqman Chuah (2012)
Helical and straight CNFs are prepared using Floating Catalyst- Chemical Vapor Deposition (FC-CVD) from decomposition of ethanol as carbon source, hydrogen as carrier gas and argon as purge gas. The effect of reactor temperature (700 - 950°C) and hydrogen flow rate (100 - 350 mL/min) on BET surface area and pore volume of CNFs and the correlation of these properties onto their adsorption capacity of Methylene Blue (MB) and phenol are investigated. It is found that the increasing of reactor temperature and hydrogen flow rate negatively affect the development of the BET surface area and pore volume. CNFs having maximum BET surface area and pore volume can be synthesized at low reactor temperature and low hydrogen flow rate which are 700°C and 150 mL/min, respectively. The highest BET surface area and pore volume are achieved at 89 m2/g and 0.1927 cm3/g, accordingly. Meanwhile, the highest adsorption capacity of CNFs for 10 mg/L ME and phenol are achieved at 32 mg/g and 12.68 mg/g, respectively, at reactor temperature of 700°C and hydrogen flow rate of 150 mL/min. Nonetheless, the adsorption capacity of CNFs using MB and phenol is not completely consistent with the relationship between surface area and pore volume due to other factors such a surface chemistry of CNFs and the functional groups of adsorbates.